Book review of The Crisis of the European Union. Identity, Citizenship, and Solidarity Reassessed edited by Loredana Radu, Alina Bârgãoanu and Nicoleta Corbu. Bucharest: Comunicare.ro, 2013, 311 pages - Bianca Robescu (Romanian Journal of Communications and Public Relations, 2015)
The Crisis of the European Union. Identity, Citizenship, and Solidarity Reassessed explores very popular and very sensitive subjects such as the solidarity of member states, the dichotomy between the “centre” and the “periphery” of the EU, the European identity, and possible solutions to the crisis. The authors of the 11 chapters have joined forces to depict a complete picture of the aspects related to the European crisis.